Processamento e avaliação nutricional da farinha de resíduo de camarão para frangos de corte - Azevedo, Marise Stela Paes de (2014)
Two experiments were conducted in NEAVI ( Center for Studies in Poultry ) located in the Central Animal Laboratory of the Federal University of Sergipe , in order to develop a practical and inexpensive technology for the production of shrimp waste meal, as well as evaluating the content of digestible amino acids and their energy values . This study aimed to determine drying times in different proportions of shrimp waste . 35 and 50 kg of shrimp waste , in duplicate , totaling 40.70 and 100 kg , respectively, the amounts of 20 were allocated into six platforms . The time taken to dryness the residue was 35 , 45 and 55 hours, respectively. Chemical composition of shrimp head meal ( FRC ) was also evaluated and the following results were obtained : 90.7 % dry matter , crude protein 39.3 % , ether extract 5.8% , calcium 11.3 % , phosphorus 2.23 % calcium and 1 , 47 % and shrimp waste flour showed values of 89.0 % for dry matter , 32.6 % crude protein , 3.9% for fat , 9 , 87 % for calcium, phosphorus and 2.22 % to 1.53 % for sódio.No first experiment we determined the digestibility of amino acids using the method of ileal collection with 180 broiler chicks , 28 days old , distributed in a completely randomized experimental design , divided into 3 treatments with 6 replicates and 10 birds per experimental unit . The experimental diets were composed of free protein diet with 0 , 5, 10 and 15% inclusion of FRC . The best coefficients were obtained with the 10% level of inclusion for methionine ( 81.2 % ) , cystine ( 58.6 % ) , methionine + cystine ( 73.1 % ) , lysine ( 82.4 % ) and threonine ( 53.3 %). The second experiment determined the coefficients of metabolization of DM, CP , N , Gord , Ca and P and the apparent metabolizable energy (AME ) and apparent metabolizable energy corrected for nitrogen balance ( AMEn ) of test diets and food . The method of total excreta collection with 180 broiler chicks of cobb trademark , aged 16-26 days old was used . The completely randomized design with 5 treatments and 6 replicates 6 birds per experimental unit was used . The FRC was included in a reference diet at levels of 0 , 5 , 10 , 15 and 20 % . The chicks were housed in metal cage with trays to collect excreta . A significant influence of the inclusion levels of CRP (P <0.05 ) in the level of 10% was higher in the following factors : dry matter was obtained 73.27% and 76.37 % crude protein . The coefficient of metabolizable ether extract was higher in the inclusions of iv 15 % with coefficients of 95.48 % and 20 % which was 96.59 % . Nitrogen retention was higher in higher levels of inclusion of FRC 10 , 15 and 20 % , which did not differ , obtaining values of 74.3 , 77.0 and 76.9 % , respectively . No statistical difference was observed in the coefficients metabolization of calcium and phosphorus . The AME and AMEn were significantly affected by the inclusion of FRC , as was increased to include these variables suffered diminishing effect on their values . The best level was 10% which presented values of AME 2325.1 Kcal / Kg and AMEn 1827.5 Kcal / Kg for flour of shrimp waste .